2022
DOI: 10.3390/ijerph192315458
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Temperament and Character, Parental Stress, and Mental Health Problems with Attachment Disorders among Children

Abstract: According to Cloninger’s model, personality is conceptualized in temperament and character traits contributing to a child’s psychosocial development. Additionally, parent–child interaction is important for the child’s socio-emotional development. To date, the relationship between attachment and temperament and character for child mental health development and its effects on parents remains mostly unclear. The aim of the present study was thus to examine the relationship of attachment, temperament and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…9 Studies have shown that parent-reported difficult temperament in infancy and toddlerhood is associated with greater psychopathology in childhood and adolescence, greater depression, lower wellbeing, and unemployment in adulthood. [10][11][12][13][14][15] Children with difficult temperaments often struggle to regulate their emotions and behaviors, which can lead to difficulties in forming and maintaining positive relationships with peers, teachers, and family members. Over time, these interpersonal challenges can contribute to social withdrawal, loneliness, and even social rejection, which may persist into adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Studies have shown that parent-reported difficult temperament in infancy and toddlerhood is associated with greater psychopathology in childhood and adolescence, greater depression, lower wellbeing, and unemployment in adulthood. [10][11][12][13][14][15] Children with difficult temperaments often struggle to regulate their emotions and behaviors, which can lead to difficulties in forming and maintaining positive relationships with peers, teachers, and family members. Over time, these interpersonal challenges can contribute to social withdrawal, loneliness, and even social rejection, which may persist into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, these interpersonal challenges can contribute to social withdrawal, loneliness, and even social rejection, which may persist into adulthood. [10][11][12][13][14][15] Furthermore, difficult temperament in childhood is associated with an increased risk of developing internalizing and externalizing problems such as anxiety, depression, and conduct disorder. These mental health difficulties can have long-term consequences for individuals' educational attainment, employment prospects, and overall well-being in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Parental reports are often used to measure child temperament due to the unsuitability of self-report in young children and the costs and poor reliability of child observations (9). A parent reported di cult temperament in infancy and toddlerhood is associated with greater psychopathology in childhood and adolescence and greater depression, lower wellbeing, and unemployment in adulthood (10)(11)(12)(13)(14)(15). Understanding the current prevalence of di cult temperament and associated risk factors is important for early identi cation and targeted interventions (10).…”
Section: Introductionmentioning
confidence: 99%